Pelatihan Inovasi Agribisnis untuk Peningkatan Pendapatan Petani di Desa Adirejo - Ihsan Mustofa; Subandi; Astri Shabrina; Apriyadi Wardhana (Institut Agama Islam Ma’arif NU (IAIMNU) Metro Lampung, 2023)
Abstract The agribusiness innovation training was carried out because the exchange rate for farmers is still very low in Indonesia in 2021, for example DKI Jakarta which experienced a decline and Kalimantan which experienced an insignificant increase, this will have an impact on the income of farmers who are unable to meet the needs of their families and work because every year the need for living always increases, therefore this service is carried out with the aim of increasing agribusiness innovation for farmers. Another goal to be achieved in this service is increasing farmers' income. This service uses training as a method by implementing innovation theory in the field of agribusiness, innovation theory is used to collaborate technology in carrying out farmers' agribusiness activities. The application of technology as innovation will produce great benefits for agribusiness results. The findings in this service resulted in farmers getting benefits, namely being able to implement agribusiness innovations so that they were able to increase yields and production and improve the quality of production results. An increase in yield and quality will in a straight line increase the exchange value of farmers' produce to increase the income they will receive.